2020
DOI: 10.31224/osf.io/jqytk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small-scale Geotechnical Testing Using a Six-axis Robot

Abstract: Single-gravity (1-g) small-scale testing is a widely used method to investigate geomechanics problems that involve the interactions between soils and objects (e.g., structures or machine parts). This letter presents a new approach for performing 1-g model tests where a six-axis industrial robot functions as a versatile actuator capable of moving objects along virtually arbitrary trajectories, while simultaneously tracking multiple components of force and moment acting on the objects. A performance evaluation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…Both of these studies observed increasing drag force fluctuations with an increasing initial packing fraction of the granular beds. Similar force fluctuations were observed by Kashizadeh and Hambleton 63 on reduced-order modeling of the plowing processes in sands and by Jin et al 64 in the development of a new single-gravity (1-g) small scale testing methodology. As this phenomenon directly relates to the changing density of the media, we use the more detailed DPM model for this case.…”
Section: Drag Variations In the Plowing Of Granular Mediasupporting
confidence: 81%
“…Both of these studies observed increasing drag force fluctuations with an increasing initial packing fraction of the granular beds. Similar force fluctuations were observed by Kashizadeh and Hambleton 63 on reduced-order modeling of the plowing processes in sands and by Jin et al 64 in the development of a new single-gravity (1-g) small scale testing methodology. As this phenomenon directly relates to the changing density of the media, we use the more detailed DPM model for this case.…”
Section: Drag Variations In the Plowing Of Granular Mediasupporting
confidence: 81%